2005
DOI: 10.1523/jneurosci.4065-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Uniquely Selective Inhibitor of the Mammalian Fetal Neuromuscular Nicotinic Acetylcholine Receptor

Abstract: We have purified and characterized a novel conotoxin from the venom of Conus obscurus, which has the unique property of selectively and potently inhibiting the fetal form of the mammalian neuromuscular nicotinic acetylcholine receptor (nAChR) (␣1␤1␥␦-subunits). Although this conotoxin, ␣A-conotoxin OIVB (␣A-OIVB), is a high-affinity antagonist (IC 50 of 56 nM) of the fetal muscle nAChR, it has Ͼ1800-fold lower affinity for the adult muscle nAChR (␣1␤1⑀␦-subunits) and virtually no inhibitory activity at a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Binding of a single a-Ctx molecule to a nAChR subunit interface is sufficient to block the allosteric transitions required for ion channel opening (Talley et al, 2006), and binding to a target site can occur with high affinity without regard to composition of other binding sites in the receptor complex. Examples include inhibition of one of five sites in an a7 homopentamer, binding to the a-« or a-d interface in a muscle type nAChR, or binding to the a6-b2 interface in an a6b2a4b2b3 nAChR (Groebe et al, 1995;Sine et al, 1995;Jacobsen et al, 1999;Gotti et al, 2005;Teichert et al, 2005). Thus, the affinities of the LvIA and BuIA analogs for their respective binding would be expected to be similar for a mixed b2 and b4 nAChR subtype.…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…Binding of a single a-Ctx molecule to a nAChR subunit interface is sufficient to block the allosteric transitions required for ion channel opening (Talley et al, 2006), and binding to a target site can occur with high affinity without regard to composition of other binding sites in the receptor complex. Examples include inhibition of one of five sites in an a7 homopentamer, binding to the a-« or a-d interface in a muscle type nAChR, or binding to the a6-b2 interface in an a6b2a4b2b3 nAChR (Groebe et al, 1995;Sine et al, 1995;Jacobsen et al, 1999;Gotti et al, 2005;Teichert et al, 2005). Thus, the affinities of the LvIA and BuIA analogs for their respective binding would be expected to be similar for a mixed b2 and b4 nAChR subtype.…”
Section: A-conotoxins Identify A3b4 Nachrs In Chromaffin Cellsmentioning
confidence: 99%
“…However, another possible cause of EPC prolongation after block of synaptic activity is postsynaptic upregulation of fetal-type AChRs (Kues et al, 1995), which have a longer mean open time (Sakmann and Brenner, 1978;Fischbach and Schuetze, 1980). To examine the contribution of fetal-type AChRs to prolongation of EPC decay, we selectively blocked fetal-type AChRs using a recently discovered toxin that is selective for fetal-type AChRs (␣A-conotoxin OIVA[K15N]) (Teichert et al, 2005(Teichert et al, , 2006. Before using ␣A-conotoxin OIVA[K15N] on muscle after blockade of synaptic activity, we confirmed that it had no effect on control muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the contribution of fetal-type AChRs to EPCs and miniature EPCs (MEPCs) was performed by measuring EPCs and MEPCs in individual muscles before and after application ␣A-conotoxin OIVA[K15N] [synthesized as described previously (Teichert et al, 2005(Teichert et al, , 2006]. After recording from endplates in control Ringer's solution, ␣A-conotoxin OIVA[K15N] was added to 20 ml of Ringer's solution at a final concentration of 1 M, and this solution was bubbled continuously with 95% O 2 /5% CO 2 and recirculated throughout the bath.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the ε-subunit was assembled into functional AChRs during embryonic stages, we measured EPPs in response to distinct toxins that specifically recognize the γ-AChRs [αA-conotoxin OIVB or αA-OIVB (Teichert et al, 2005)] and ε-AChRs [waglerin 1 (McArdle et al, 1999)]. As shown in Fig.…”
Section: Delayed Occurrence Of Achr Clusters In γmentioning
confidence: 99%